SYSTEMATIC LITERATURE REVIEW: DAMPAK PENDIDIKAN GRATIS TERHADAP KUALITAS PENDIDIKAN DI LEMBAGA PENDIDIKAN - Muhibburrohman, Ohib; Fauzi, Anis; Hidayat, Wahyu; Syarifudin, Encep; Hanafi, Hanafi (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2024)
The purpose of this study is to provide knowledge about the analysis of existing literature in the past five years about the impact of free education policies on the quality of education. To achieve this goal, the researcher uses the Systematic Literature Review method. The method of collecting various literature on the intended study is the impact of the free education policy and reviewing the results of the topic of the literature. The method is carried out through the stages of (1) collecting literature data, (2) selecting literature data, (3) reviewing literature data, (4) concluding the results of literature review, and (5) discussing and collecting additional data. This study uses the PICO (population, intervention, comparator, and outcome) framework, to search for appropriate literature. So the research question (RQ) in this study is how does free education impact on the quality of education in educational institutions? From the systematics that have been made, the results are obtained that the author assesses that the free education policy has an impact on the quality of education. Some educational institutions have produced positive impacts and some institutions have had impacts that are not in accordance with the goals of the free education policy.